Bearing the Cost of Stored Carbon Leakage - Vinca, Adriano; Emmerling, Johannes; Tavoni, Massimo (Frontiers in Energy Research, 2018)
Carbon capture and sequestration (CCS) is considered a key technology for stabilizing climate change. However, leakage of CO2 from stored carbon can potentially undermine the value of carbon storage as a mitigation option. Thus, monitoring and verifiability of CO2 storage should be encouraged through policy provisions such as accounting and pricing of leaked emissions. Here we assess different institutional and economic mechanisms for accounting for carbon leakage. Using an integrated assessment model we quantify the impacts on the climate, the economy and the mitigation strategies. Results show that carbon leakage can reduce the share of fossil based CCS by up to 35%, if it is controlled and correctly priced. Biomass based CCS is less affected. Accounting for leakage leads to an increase of climate policy costs of up to 0.4 percentage points due to increased emissions.